Language Ideologies of Young Chinese Surabayanese’ Motivation in Learning Mandarin in Post Suharto Era - Gabriela Angeline Hananya (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
This is the study of language ideologies of young Chinese Surabayanese’ motivation in learning Mandarin and the influence of their beliefs in Mandarin towards their sense of Chinese-ness. The approach of this study is qualitative, through semi-structured interviews and participant observation. There are four young Chinese Surabayanese participated in this study. It is found that they perceived learning Mandarin is an advantage. This advantage is then explained through their beliefs about Mandarin in four supportive points: globalising life opportunities in working and communication, mastering Mandarin caused by the rise of China, investing in their linguistic capital, and parents’ influence. Though there are two participants who feel more Chinese after learning Mandarin, but it is never their intention to be more Chinese when they start learning Mandarin. In the end, their ideology of learning Mandarin mainly focuses with the benefit and advantage instead of with their sense of Chinese-ness.